Documentação de experiências artísticas em livros de artista - Machado, Bárbara Tavares Schiavon (Revista do Colóquio, 2020)
This article investigates single and circumstantial artistic experiences registered by documentation in books, throuth the writing in report way, as preparation for the action and/or for subsequent digression. Presents as study Flávio de Carvalho’s and the duo André Severo & Maria Helena Bernardes’ works, so well circumscribed on the serie Documento Areal, books physically ordinary that reach the work of art state while document the artistic process.
Keywords: report way, artist’s writing, documentation, artist’s books, experience